PISA : politique, problèmes fondamentaux et résultats paradoxaux - Svein Sjøberg (Nantes Université, 2012)
The PISA project has in the last decade steadily increased its influence on educational policies in participating countries. Tables of PISA scores and country rankings are often taken at face value, not only in media, but also by policymakers and politicians. This article will raise some of the concerns that would require further. I will start by raising some basic questions about why OECD has initiated the PISA project. The intentions of PISA are, not surprisingly, strongly related to the overall political aims OECD and the underlying commitment to a competitive global free market economy. Examples are given on how PISA exerts influence on educational policy. Then I will provide critical points of two categories. The first category relates to the PISA project as such. I will argue that it is impossible to construct a test that in a fair and objective way can be used across countries and cultures. The requirement of "fair testing" implies by necessity that all local, current and topical issues must be excluded. This runs against most current thinking in e.g. science education, where "science in context" and "a localized curriculum" are ideals promoted by e.g. UNESCO, educators as well as in many national curricula. The second category of critical points relates to some of the rather intriguing results: It seems that pupils in high-scoring countries also develop the most negative attitudes to the subject. It also seems that PISA scores are unrelated to educational resources, class size etc. PISA scores also seem to be negatively related to the use of active teaching methods, inquiry based instruction and the use of ICT. Whether one believes in PISA or not, such intriguing results need to be discussed.